(untitled) (Scientific Journal of Research Studies in Future Management, 2023)
This research was formed with the aim of designing a structural model of the relationship between intelligent leadership and organizational silence with the mediating role of the receiving team of managers. This research was a type of descriptive-correlational research. The statistical population in this research was opinionated and expert people, executive managers and employees in city insurance companies, and the sampling method was accessible and the sample size was based on Morgan's table of 385 people, and the questionnaire was made by the researcher of the research, whose psychological characteristics has it. It was approved and completed. Based on the structural equation model, the findings showed that the receivers' team has a mediating role in relation to intelligent leadership and organizational silence, and in addition to the direct relationship of 0.34 between intelligent leadership and organizational silence, this amount can be explained by examining the mediation of the change of managers' team adaptability. It reaches 0.491. These results indicated that intelligent leadership is an important factor in productivity and improving conditions in the organization.